Incidence de la culture politique sur le résultat des élections en province orientale : cas de la ville de Kisangani de 2006 à 2011 - FUMBA LITEMBU mwenga LIPANDA Sylvain (IJRDO - Journal of Social Science and Humanities Research, 2020)
it is paradoxical to note that while constituting the center of activities in all human societies, the political field is that which is the subject of the flattest and least thought out ideas. Some have even come to the conclusion that adventurers are more successful in politics. This is therefore the area where big extravagances are enthroned where manifestly absurd beliefs bind magnificently even lucid minds, where coarse lies can lead whole populations towards behaviors that destroy their own spaces. It should be noted that the Congolese people and their elected officials suffer from the absence of a democratic political culture. This precarious situation left a deep impression on us. Given that in political matters, it is difficult to judge people without knowing their political culture.